REVIEW OF CITY PARKS IN TERMS OF DISABLED RIGHTS - Cetıslı-korkmaz, Nılufer; Bılek, Furkan; Huzmeli, Esra Dogru; Gökçek, Özden (My University, 2021)
The creation and presentation of independent and individual spaces for disabled individuals is the most important step of social integration. The main purpose of this report is to investigate whether some city parks in Turkey are suitable or not for the use of disabled individuals. This descriptive research includes the perception of disabled individuals about the city parks in Hatay, Şanlıurfa and Gaziantep provinces. Individuals with disabilities assessed the structure of city parks, ease of use, ergonomics and basic needs with basic 22- questions. The questions focused on respondents' experiences with specific destinations and environmental barriers. 150 disabled individuals, 53 from Hatay, 53 from Şanlıurfa and 44 from Gaziantep, were included in the study. Participants; 29.3% were using wheelchairs, 34% were using electric wheelchairs, 30% were using crutches and 6.7% were not using assistive devices. As a result of the study, it was seen that the parks were not convenient and useful for the disabled individuals. Deficiencies in city parks can avoid evaluating and ensuring the leisure time activities, social compliance and exercise activities for disabled individuals. Thus, we think that these environments can maximize opportunities for leisure activities and social participation by individuals with lifelong disabilities.
Keywords: Sağlık Politikaları ve Hizmetleri